The Relationsip Between Corporate Social Responsibility Through Financial Reporting Quality - FIRDAUS, Rizalnur; DOLOKSARIBU, Tio Arriela; HERNANIK, Nova Dwi (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study aims to examine the impact of Corporate Social Responsibility on the Quality of Financial Reporting in manufacturing companies in Indonesia. The research sample consisted of 75 manufacturing companies that were observed from 2017 to 2019. This study uses a regression data panel to test the effect of Corporate Social Responsibility (CSR) which is calculated by using a dummy variable on the Quality of Financial Reporting (FRQ) which uses a measure consisting of value relevance (VR), acrual quality (AQ) and earning persistence (EP). The results of research on manufacturing companies in Indonesia indicate that there is a positive and significant relationship between Corporate Social Responsibility and value relevance. The results of research on manufacturing companies in Indonesia indicate that there is a positive and significant relationship between Corporate Social Responsibility and accrual quality. The results of research on manufacturing companies in Indonesia show that there is a positive and significant relationship between Corporate Social Responsibility and earning persistence.